Forced to Freedom? Empirical Relations between Aid and Economic Freedom - Tobias Knedlik; Franz Kronthaler (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2006)
The paper explores the relationships between economic freedom on the one side and development aid and IMF credit as approximation for conditional aid on the other side. After a short review of current literature on the issue of economic development, economic freedom, aid, and IMF credit, the paper develops a simple panel regression model to evaluate the relationship between “economic freedom” as dependent variable and “aid” and “IMF credit” as independent variables. The estimation is based upon data taken from the World Bank's World Development Indicators and the Heritage Index of Economic Freedom. In contrast to previous research, our results allow the rejection of the hypothesis that IMF credit increases economic freedom and that aid is not contributing to economic freedom. The estimation results suggest that, firstly, aid is positively correlated with economic freedom, and secondly, that IMF credit is negatively correlated with economic freedom. Taking IMF credit as proxy for conditional aid, we conclude that for the period of observation it could not be shown that countries can be forced to economic freedom by aid conditions. – – Der Beitrag untersucht die empirischen Beziehungen zwischen ökonomischer Freiheit einerseits und allgemeiner Entwicklungshilfe bzw. IWF-Krediten als Approximation für konditionierte Entwicklungshilfe andererseits. Dazu wird zunächst die aktuelle Literatur zu Fragen der ökonomischen Entwicklung, der ökonomischen Freiheit, finanzieller Entwicklungshilfe und IWF-Krediten dargestellt. Ein einfaches Panel-Regressionsmodell, mit "ökonomischer Freiheit" als abhängiger Variable und "allgemeiner Entwicklungshilfe" und IWF-Kredite" als unabhängige Variablen, dient dann als Ausgangspunkt für die empirische Untersuchung. Die Daten wurden aus dem World Development Indicators-Datensatz der Weltbank und aus dem Heritage Index der ökonomischen Freiheit gewonnen. Im Gegensatz zu früheren Untersuchungen können wir die Hypothesen, dass allgemeine Entwicklungshilfe freiheitsbegrenzend wirkt während IWF-Kredite die ökonomische Freiheit erhöhen, ablehnen. Unsere Schätzergebnisse zeigen, dass allgemeine Entwicklungshilfe positiv und IWF-Kredite negativ mit ökonomischer Freiheit korreliert sind. Es zeigt sich, dass Länder mit Hilfe von konditionierter Entwicklungshilfe nicht zu ökonomischer Freiheit gezwungen werden können.
urn:nbn:de:gbv:3:2-2010
Keywords: P10; O19; F35; 330; Ökonomische Freiheit; Entwicklungshilfe; IMF-Kredite; wirtschaftliche Entwicklung; aid; economic freedom; IMF credit; economic development